Comparative transcriptomics unravels prodigiosin's potential cancer-specific activity between human small airway epithelial cells and lung adenocarcinoma cells - Davient, Bala (2018)
Objective: Non-Small Cell Lung Cancer (NSCLC) is extremely lethal upon metastasis and requires safe and effective systemic therapies to improve a patient's prognosis. Prodigiosin (PG) appears to selectively and effectively target cancer but not healthy cells. However, PG's cancer-specific activity has remained elusive until recently.